Training and Supervision for Counselling in Action - Dryden, Windy; Thorne, Brian, 1937- (London : Sage, 1991)
Examines the issues involved both in the training and supervision of counsellors and in the preparation of those who are to undertake supervisory and training roles. The text discusses the responsibilities, professional issues and practical approaches involved.
Includes index.
Keywords: Counseling -- Study and teaching; Counselors -- Supervision of